Religious diversity and the problem of systemic racism in the context of global migration: A case study of Tunisia's treatment of sub-Saharan black Christians - Krašovec, Primož; Zalta, Anja (Poligrafi, 2024)
The article is based on several months of research into the process of racialisation of sub-Saharan migrants in Tunisia. The starting point of our research is the speech of Tunisian President Kais Saied in February 2023. In light of the new negotiations with the EU on support for migration management in the Mediterranean, the president emphasised how important it is for Tunisia to be and remain Arab and Muslim. The sub-Saharan migrants who come to Tunisia are black, many of them are also Christians. The Tunisian case of racialisation of migrants is similar to the dynamics of systemic racism in EU. Our thesis is that racialisation is part of a more complex dynamic determined by the capitalist mode of production, which, due to its internal contradictions, simultaneously demands and excludes human labor power. We argue that the permanently excluded represent a surplus population that, because it is not disciplined by capitalist markets, is considered dangerous and thus falls under the jurisdiction of the police. This process of policing surplus populations represents contemporary systemic racism, with »race« being the result of said process and not determined by its biological, religious, ethnic, or cultural characteristics. We support our thesis with a field study. It consists of qualitative interviews with Tunisian experts and three personal narrative interviews with sub-Saharan migrants from Cameroon.